2013
DOI: 10.4093/dmj.2013.37.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Epidemics in Korea: Reappraise Nationwide Survey of Diabetes "Diabetes in Korea 2007"

Abstract: There are many studies on the prevalence, clinical characteristics, and economic burden of diabetes across the past four decades in Korea. Nonetheless, there is a dearth of nationwide study regarding diabetes encompassing all age group. Eight years ago, the Committee on the Epidemiology of Diabetes Mellitus of Korean Diabetes Association collaborated with Health Insurance Review & Assessment Service to evaluate the status of diabetes care and characteristics in diabetic patients in Korea. In 2007, the collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 11 publications
1
56
2
Order By: Relevance
“…The accuracy of diagnoses in claim databases is debatable. Recent Korean studies that compared diagnoses from claim databases with medical records observed overall accuracy rates of 72.3% for diabetes, 71.4% for myocardial infarction and 83.4% for ischaemic stroke . There was a possibility of non‐differential misclassification which would bias the risk ratio toward the null.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of diagnoses in claim databases is debatable. Recent Korean studies that compared diagnoses from claim databases with medical records observed overall accuracy rates of 72.3% for diabetes, 71.4% for myocardial infarction and 83.4% for ischaemic stroke . There was a possibility of non‐differential misclassification which would bias the risk ratio toward the null.…”
Section: Discussionmentioning
confidence: 99%
“…From the Korea National Health and Nutrition Examination Survey (KNHANES) III (2005), adequate glycemic control was achieved in 43.5% and 22.9% of diabetic patients, with A1c levels <7.0% and <6.5%, respectively [5]. As is shown by similar results from a study using the health insurance data from the Health Insurance Review & Assessment Service, only 40.3% of patients managed to maintain their blood glucose level below 7.0% [6]. Thus, more than half of diabetic patients are exposed to the threat of chronic complications secondary to persistent hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of Type 2 diabetes and prediabetes is increasing rapidly and is a growing health problem in both developed and developing countries . To overcome the burden of this epidemic, strategies for effective prevention by earlier identification of people at high risk of developing diabetes are becoming more important.…”
Section: Introductionmentioning
confidence: 99%